Recombinant vaccinia virus induces neutralising antibodies in rabbits against Epstein-Barr virus membrane antigen gp340. - Mackett, M (1985)
The Epstein-Barr virus membrane antigen gene gp340 was isolated, inserted into several strains of vaccinia virus and expressed under the control of a vaccinia virus promoter. The EBV-derived protein which was produced by the recombinant vaccinia viruses was heavily glycosylated, readily labelled with threonine, could be detected at the surface of infected cells and had a mol. wt. of approximately 340 kd, all of which are properties of the authentic gp340. Polyclonal rabbit antisera against gp340 and an EBV-neutralising anti-gp340 monoclonal antibody both recognised cells infected with the recombinant vaccinia viruses. Moreover, rabbits vaccinated with one of the recombinants produced antibodies that recognised EBV-containing lymphoblastoid cells and neutralised EBV.